India: Country brief - HarvestPlus (International Food Policy Research Institute, 2015)
HarvestPlus improves nutrition and public health in India by promoting pearl millet that provides more iron and wheat that provides more zinc in the diet. We work with more than 70 partners drawn from government, business, and civil society.